An Address to Catholic Employers (Relations industrielles / Industrial Relations, 1949)
In view of the great and general interest aruused by a French-language discourse of His Holiness Pop e Pius XII to delegates attending the Rome Congress of the International Union of Catholic Employers Associations, on May 7th, 1949, the comple text is presented herewith.